Highly selective hydrogen production from propane by RuâNi coreâshell nanocatalyst deposited on reduced graphene oxide by sequential chemical vapor deposition - Mehravar, S. (John Wiley and Sons Ltd, 2020)
A narrow temperature window (160Â°C-190Â°C) was identified for the selective deposition of Ru on Ni supported on reduced graphene oxide (rGO) through a sequential chemical vapor deposition (CVD) method. Cyclopentadiene and cyclopentene were identified as decomposition products of nickelocene CVD on rGO, whereas only methane was detected in gaseous products from ruthenocene CVD. Heat treatment converted the selectively deposited Ru on Ni/rGO into RuâNi coreâshell bimetallic system on the surface of rGO as confirmed by high-resolution transmission electron microscopy. The RuâNi/rGO thus prepared produced hydrogen with high selectivity in propane steam reforming performed in the temperature range of 350Â°C to 850Â°C. Addition of 3.6 Ru against Ni supported on rGO improved the turnover frequency (TOF) of propane up to 70 to 100 compared to the Ni/rGO catalyst at lower temperatures (350Â°C-450Â°C). The presence of Ru lowered the activation energy of propane SR from 65.7 kJ molâ1 for Ni/rGO to 48.7 kJ molâ1 for RuâNi/rGO catalyst. Â© 2020 John Wiley & Sons Ltd